The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7717/peerj.5500
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of perceptions of nuts between the general public, dietitians, general practitioners, and nurses

Abstract: BackgroundNut consumption at the population level remains low despite the well-documented benefits of their consumption, including their cardioprotective effects. Studies have suggested that advice from health professionals may be a means to increase nut consumption levels. Understanding how nuts are perceived by the public and health professionals, along with understanding the public’s perceptions of motivators of and deterrents to consuming nuts, may inform the development of initiatives to improve on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…This approach may have implications for nutrition labelling and could alleviate the well-documented confusion surrounding nuts and body weight. 12,14 In comparison to the Atwater system, which uses predetermined energy values for each energy-yielding macronutrient or proximate (alcohol, carbohydrate, fat, protein) to estimate the total energy content of a food/ beverage, metabolisable energy is defined as the amount of energy that has been absorbed by the body. The lower metabolisable energy of nuts compared with that estimated by Atwater factors has been suggested to be due to the physical encapsulation of some of the fat content within cell walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach may have implications for nutrition labelling and could alleviate the well-documented confusion surrounding nuts and body weight. 12,14 In comparison to the Atwater system, which uses predetermined energy values for each energy-yielding macronutrient or proximate (alcohol, carbohydrate, fat, protein) to estimate the total energy content of a food/ beverage, metabolisable energy is defined as the amount of energy that has been absorbed by the body. The lower metabolisable energy of nuts compared with that estimated by Atwater factors has been suggested to be due to the physical encapsulation of some of the fat content within cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both consumers and health professionals report believing that regular nut consumption will lead to weight gain due to their high-fat content. [12][13][14][15] However, substantial evidence has shown no association between nut intake and body weight. 6,16,17 A systematic review of randomised controlled trials concluded that nut consumption did not influence body weight when compared with nut-free diets, and, in fact, isocaloric substitutions of nuts resulted in decreased body fat compared with control diets.…”
Section: Introductionmentioning
confidence: 99%
“…Nuts are energy-dense foods, and both consumers and health professionals report concern regarding their impact on body weight (31,37,38) . As a result, it is pertinent to explore the relationship between nut consumption and anthropometric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The most extended feeling about nut consumption is the belief that eating nuts would cause weight gain, despite the cumulative results reporting no effect on it [ 51 , 76 , 78 , 85 ]. An interesting and recent study that evidence this issue was that developed by Brown et al [ 141 ], who evaluated the nut perceptions among the general public. Results revealed that over half the respondents reported they would eat more nuts if they were advised to do it by a dietitian or doctor, and the most frequently selected deterrent to increasing nut consumption was the potential weight gain (66%).…”
Section: Barriers and Facilitators To Pistachio Consumptionmentioning
confidence: 99%
“…Another common barrier to nut consumption was their high cost. The study developed by Brown et al [ 141 ] in 710 people found the cost (67%) as the most frequently selected deterrent to increase nut intake. Recently, a survey of 124 participants from the United States [ 143 ] highlighted an inverse relationship between the price and the intention to consume nuts.…”
Section: Barriers and Facilitators To Pistachio Consumptionmentioning
confidence: 99%